Potential role of CTNNA3 and FRMPD4 in vascular tumorous thrombosis of colon adenocarcinoma - Bin Liu; Yu Xiang; Weihua Guo (Indian Journal of Pathology and Microbiology)
Background: Vascular tumorous thrombosis is a crucial pathological feature of malignant tumors that is closely associated with lymph node metastasis and is considered a form of tumor micrometastasis. Two downregulated genes, catenin alpha 3 (CTNNA3) and FERM and PDZ domain-containing 4 (FRMPD4), were selected by analyzing the differential expression of vascular tumorous thrombus in colon adenocarcinoma and paracancerous tissues. Further investigation revealed their potential role in the development of vascular tumorous thrombosis in colon adenocarcinomas. Materials and Methods: Candidate genes for vascular tumorous thrombosis in colon adenocarcinoma were screened using GSE127069, and pan-cancer verification and immune infiltration analysis were performed. The relationship between gene expression and vascular tumorous thrombosis was analyzed based on the level of gene mutations using cBioPortal. Finally, the collected clinical samples were used to verify expression. Results: CTNNA3 and FRMPD4 were expressed at low levels in the vascular tumorous thrombosis of colon adenocarcinoma and positively correlated with microsatellite instability. They are also closely related to the immune microenvironment and the infiltration of immune cell subtypes. Based on gene mutation analysis, gene deletion is suggested to be related to vascular invasion indicators. Finally, protein and messenger ribonucleic acid (mRNA) expression of CTNNA3 and FRMPD4 were downregulated in the vascular tumorous thrombosis samples of colon adenocarcinoma compared to normal glands from paracancerous tissues. Conclusion: Our study suggests that CTNNA3 and FRMPD4 could be promising biomarkers for vascular tumorous thrombosis in colon adenocarcinoma, potentially enabling the identification of micrometastases in this type of cancer. These findings suggest a novel strategy for the detection and management of colon adenocarcinomas.